(untitled) (Analysis in Theory and Applications, 2020)
The main interests here are to study the relationship between card(X) and card(P(X)) and the connection between the separability of a space X and cardinality of some function space on it. We will convert the calculation of card(P(X)) to the calculation of card(F(X→ Q)).The main tool we used here is Zorn Lemma.